2007
DOI: 10.5424/srf/2007161-01001
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the electroantennographic response by Cerambyx welensii Küster and Prinobius germari Germar (Coleoptera: Cerambycidae) to olfactory stimuly

Abstract: IntroducciónLa acción de los cerambícidos xilófagos, principalmente los géneros Cerambyx y Prinobius, se ha considerado un factor desencadenante y/o agravante en el problema de la «seca» del género Quercus en nuestro país (Montoya, 1992;Muñoz et al., 1996;Navarro et al., 2004). A pesar de ello, se desconoce la importancia real del papel que desempeñan en el decaimiento de las formaciones forestales donde la encina y el alcornoque son especies arbóreas dominantes, en especial las dehesas y los alcornocales. A e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 40 publications
0
9
1
Order By: Relevance
“…Sánchez-Osorio et al (2008) found limonene emission from Q. suber leaves to be higher in trees heavily colonized by C. welensii than neighboring non-colonized trees. Further, (+)-Limonene and two related compounds (α-phellandrene and α-terpinene) elicited moderate EAG responses in P. myardi, high concentrations of α-phellandrene having been found in leaf emissions from Q. ilex (Llusià et al 2012).…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…Sánchez-Osorio et al (2008) found limonene emission from Q. suber leaves to be higher in trees heavily colonized by C. welensii than neighboring non-colonized trees. Further, (+)-Limonene and two related compounds (α-phellandrene and α-terpinene) elicited moderate EAG responses in P. myardi, high concentrations of α-phellandrene having been found in leaf emissions from Q. ilex (Llusià et al 2012).…”
Section: Discussionmentioning
confidence: 92%
“…The main group included 16 analogues of volatiles identified in foliar emissions from Q. suber and Q. ilex: the monoterpenes, β-pinene, (+)-α-pinene, (+)-limonene, β-myrcene, 1,8-cineole, (E)-β-ocimene, α-terpinene, γ-terpinene, α-phellandrene, ρ-cymene and α-terpineol (Sánchez-Osorio et al 2008;Llusià et al 2012); the GLVs, (E)-2-hexenal, (Z)-3-hexenol and (Z)-3-hexenyl acetate (Fürstenau et al 2012); and the triterpenes, lupenone and erithrodiol (Monaco and Previtera 1984). We also tested several analogues of compounds found in Q. suber cork, namely gallic and ellagic acids, the triterpene friedelin and 3-methyl-butanol (Rocha et al 1996).…”
Section: Test Substancesmentioning
confidence: 99%
See 3 more Smart Citations